Intrarenal Reflux in the Light of Contrast-Enhanced Voiding Urosonography - Ana Simicic Majce (Frontiers in Pediatrics, 2021)
Purpose: The aim of this study was to analyze the incidence of intrarenal reflux (IRR) among vesicoureteral refluxes (VURs), diagnosed by contrast-enhanced voiding urosonography (ceVUS), to define VURs which are positive to IRR and their locations in the kidney.Materials and Methods: Seventy patients with VURs, including 103 uretero-renal units (URUs) with VURs of grades II–V (37 URUs were excluded because of renal anomalies or absence of VUR) were examined with ceVUS due to recurrent febrile UTI or first febrile UTI accompanied by abnormalities on renal ultrasonography. Patients were examined on GE Logiq S8 ultrasound machine, using second generation of ultrasound contrast agent.Results: Out of 103 VURs, 51 (49.51%) had IRR regardless the grade of VUR, showing increase in IRR incidence with VUR severity (p < 0.0001). The median age at the time of IRR diagnosis was 5 months (IQR, 3–14.3), whereas in patients without IRR, it was 15.5 months (IQR, 5–41.5), (p = 0.0069). IRR was most common in superior pole (80%), followed by inferior pole (62.7%), and middle segments (37%), and to all segments (27%) (p < 0.0001).Conclusion: In the present study, patients with IRR-associated VUR showed earlier clinical presentation. The distribution of IRRs corresponded to the natural distribution of composed papillae types II and III, while the incidence of IRR increased with severity of VUR. Further clinical studies may point to the importance of considering IRR in the future classification of VUR.